A simple pipeline for cell cycle kinetic studies in the root apical meristem. (21st March 2022) - Pasternak, Taras; Kircher, Stefan; Pérez-Pérez, José Manuel; Palme, Klaus
Abstract : A simple pipeline of marker-free histological techniques allows precise 3D mapping of cell cycle stages in the root apical meristem, enabling dynamic chromatin studies. Abstract: Root system architecture ultimately depends on precise signaling between different cells and tissues in the root apical meristem (RAM) and integration with environmental cues. This study describes a simple pipeline to simultaneously determine cellular parameters, nucleus geometry, and cell cycle kinetics in the RAM. The method uses marker-free techniques for nucleus and cell boundary detection, and 5-ethynyl-2ʹ-deoxyuridine (EdU) staining for DNA replication quantification. Based on this approach, we characterized differences in cell volume, nucleus volume, and nucleus shape across different domains of the Arabidopsis RAM. We found that DNA replication patterns were cell layer and region dependent. G2 phase duration, which varied from 3.5 h in the pericycle to more than 4.5 h in the epidermis, was found to be associated with some features of nucleus geometry. Endocycle duration was determined as the time required to achieve 100% EdU-positive cells in the elongation zone and, as such, it was estimated to be in the region of 5 h for the epidermis and cortex. This experimental pipeline could be used to precisely map cell cycle duration in the RAM of mutants and in response to environmental stress in several plant species without the need for introgressing molecular cell cycle markers.